Relationship of Patient Satisfaction With Hypertension Treatment Adherence - Suriani; Luqman (Jurnal Kesehatan Akimal, 2022)
Adherence in general is the level of a person's behavior in getting treatment, following a diet, and implementing lifestyle changes in accordance with the recommendations of health care providers with patients. Satisfaction is a person's feeling of pleasure that comes from the comparison between the pleasure of an activity and a product with his expectations. This research is descriptive correlation with cross-sectional approach. The population in this study were hypertensive patients undergoing treatment at the internal medicine polyclinic of Cut Meutia RSU, North Aceh Regency, amounting to 944 people, while the sample was 90 people. Data were collected through interviews using a questionnaire. The data were analyzed by Chie-square test using a computerized program. The results showed that of the 90 respondents, in the satisfied category, 43 people (89.6%) adhered to hypertension treatment and 5 people (10.4%) did not. And in the dissatisfied category there are 7 people (16.7%) obedient to hypertension treatment while 35 people (83.3%) are not. After statistical testing with the Chie-square test was carried out, the results were p = 0.000 (p <0.05), this means that there is a significant relationship between satisfaction and compliance with hypertension patients in undergoing treatment at BLU Cut Meutia RSU, North Aceh Regency in 2017. So it can be concluded that patient satisfaction is very necessary to achieve medication adherence. It is recommended that it can be used as a health education material and presumably can be a reference for further researchers on patient satisfaction with hypertension medication adherence.